Metaverse Marketing and Digital Consumer Purchase Behavior: Evidence from Baghdad Universities - Basheer Saadoon Hasan (Studi Akuntansi dan Bisnis Indonesia, 2026)
Purpose: The study explores how metaverse marketing affects the buying behavior of university students in Baghdad. Methodology: Descriptive-analytical design was used and a study sample of 400 students was used on an electronic questionnaire. The research hypotheses were tested by means of Pearson correlation and multiple linear regression. Results: The results showed that the metaverse marketing and purchase behavior were significantly positively related. The findings also showed that it had strong direct impacts of its four dimensions (immersion, interactivity, personalization, and digital trust) on purchase behavior. Conclusions: The findings highlight the importance of digital trust and personalization in virtual marketing environments, demonstrating their effect on students’ purchasing decisions. Limitations: The research is limited to students in Baghdad universities, which may affect generalizability to other populations. Contribution: This study offers practical guidance for marketers on leveraging metaverse platforms to influence digital consumer behavior in educational settings.